Cellular expression and function of naturally occurring variants of the human ABCG2 multidrug transporter - Zámbó, Boglárka (Cell Mol Life Sci, 2019)
The human ABCG2 multidrug transporter plays a crucial role in the absorption and excretion of xeno- and endobiotics; thus the relatively frequent polymorphic and mutant ABCG2 variants in the population may significantly alter disease conditions and pharmacological effects. Low-level or non-functional ABCG2 expression may increase individual drug toxicity, reduce cancer drug resistance, and result in hyperuricemia and gout. In the present work we have studied the cellular expression, trafficking, and function of nine naturally occurring polymorphic and mutant variants of ABCG2. A comprehensive analysis of the membrane localization, transport, and ATPase activity, as well as retention and degradation in intracellular compartments was performed. Among the examined variants, R147W and R383C showed expression and/or protein folding defects, indicating that they could indeed contribute to ABCG2 functional deficiency. These studies and the applied methods should significantly promote the exploration of the medical effects of these personal variants, promote potential therapies, and help to elucidate the specific role of the affected regions in the folding and function of the ABCG2 protein. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00018-019-03186-2) contains supplementary material, which is available to authorized users.